African Christianity : the stranger within - Galgalo, Joseph D. (Limuru, Kenya : Zapf Chancery, 2012)
What makes African Christianity Christian? What is the mission of the African church? What is the theology of the African church? What is the future of the Church in Africa or more precisely of African Christianity? Professor Galgalo gives a critical analysis of Christianity in Africa from historical, theological and sociological perspectives.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Church history; Christianity -- Africa -- Western influences; Christianity -- African influences; RELIGION -- Christian Theology -- History; Electronic books